2021
DOI: 10.1016/j.ajpc.2021.100146
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behaviour in secondary prevention of coronary artery disease: A review

Abstract: Comprehensive management of coronary artery disease (CAD) includes physical exercise as a part of daily lifestyle therapy. Still CAD patients generally have low physical activity (PA) and high sedentary behaviour (SB). This review summarizes the effect of exercise training and habitual PA and SB on physical fitness and quality of life (QoL) as well as on rehospitalizations and mortality in patients with stable CAD, recent acute coronary syndrome (ACS) or recent revascularization. A literature review of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Because CVDs are a major economic burden to the health care, exercise-based interventions provide a cost-effective way of alleviating it [ 34 ]. Also, preoperative interventions for cardiac patients, with for example an accelerometer or applications, might reduce postoperative complications [ 35 37 ]. Therefore, both pre- and postoperative rehabilitation to increase physical activity and reduce sedentary behaviour could improve postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Because CVDs are a major economic burden to the health care, exercise-based interventions provide a cost-effective way of alleviating it [ 34 ]. Also, preoperative interventions for cardiac patients, with for example an accelerometer or applications, might reduce postoperative complications [ 35 37 ]. Therefore, both pre- and postoperative rehabilitation to increase physical activity and reduce sedentary behaviour could improve postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the positive effects of physical activity prevail against several risk factors of CAD, including hypertension, the level of LDL and non-HDL cholesterol, body weight, and type 2 diabetes (Glazer et al, 2013;Winzer et al, 2018). On the other hand, having a sedentary lifestyle is one of the major risk factors for coronary artery disease worldwide (Lee et al, 2012), as well as for secondary prevention (Vasankari et al, 2021). Relatedly, several studies (Janssen et al, 2014;Meng et al, 2014) have consistently proved that interventions targeting physical activity in cardiac rehabilitation could be useful and efficient in the initiation and maintenance of physical activity among cardiac patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although other research [ 14 ] has reported the opposite results, exercise interventions in health programs improve patients’ overall health and cardiac function [ 6 , 12 ]. There is also evidence that regular moderate exercise can reduce rehospitalizations among patients with stable coronary artery disease [ 15 ], especially if it is accompanied by smoking cessation and a Mediterranean diet [ 11 ]. These results confirm that rehabilitation of CVD patients with lifestyle medicine therapy is particularly important to improve the patient’s quality of life.…”
Section: Discussionmentioning
confidence: 99%